1987
DOI: 10.1002/etc.5620060706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical structure and exposure on the microbial degradation of polycyclic aromatic hydrocarbons in freshwater and estuarine ecosystems

Abstract: The microbial mineralization of six polycyclic aromatic hydrocarbons (PAHs), containing two to five fused benzene rings, and hexadecane were investigated in sediment: water microcosms which modeled degradation in two freshwater and one estuarine ecosystem. A ranking of the PAHs by order of mineralization rates along with calculated half‐lives (range in weeks) are as follows: naphthalene (2.4‐4.4) ≥ hexadecane (2.2‐4.2) > phenanthrene (4‐18) > 2‐methylnaphthalene (14‐20) > pyrene (34‐>90) ≥ 3‐methylcholanthrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
2
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(54 citation statements)
references
References 33 publications
5
46
2
1
Order By: Relevance
“…The processes most likely to influence PAH persistence, discounting sediment transport (erosion losses, dilution with uncontaminated sediment), bioaccumulation, and bioturbation, are biological degradation by complex natural communities of bac- teria and fungi [7] and physicochemical phenomena (notably photochemical oxidation and dissolution). Microbial degradation rates for PAHs are generally higher in polluted sediments, where microbial adaption may be evident, than in pristine environments such as the Wiroa Island site of this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The processes most likely to influence PAH persistence, discounting sediment transport (erosion losses, dilution with uncontaminated sediment), bioaccumulation, and bioturbation, are biological degradation by complex natural communities of bac- teria and fungi [7] and physicochemical phenomena (notably photochemical oxidation and dissolution). Microbial degradation rates for PAHs are generally higher in polluted sediments, where microbial adaption may be evident, than in pristine environments such as the Wiroa Island site of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Microbial degradation rates for PAHs are generally higher in polluted sediments, where microbial adaption may be evident, than in pristine environments such as the Wiroa Island site of this study. Microcosm studies of microbial degradation of PAHs in aquatic ecosystems [7,13] showed that compounds with fewer than four rings degraded readily (e.g., the half-life, t 1/2 , for mineralization of PHE ϭ 4 weeks), whereas higher-molecular-weight compounds persisted much longer (e.g., BaP t 1/2 Ͼ 200 weeks), even in environments chronically exposed to petrogenic hydrocarbons. Biodegradation transformation times for naphthalene, PHE, and BaP, measured in oxidized surficial sediments of a polluted sediment (Boston Harbor, MA, USA) were 13.2 to 20, 7.9 to 19.8, and 53.7 to 82.3 d, respectively [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These products together usually accounted for less than 10% of the added [ 14 C]PAHs (data not shown). Metabolites have usually not been found to accumulate in soils and sediments, perhaps because the initial oxidation of PAHs may be the rate-limiting step in their metabolism [26][27][28] or because other members of the microbial community metabolize the intermediates via cometabolic reactions [29][30][31]. Limited metabolite accumulation may be beneficial to the environment, as early pathway metabolites are more water soluble and often more toxic than the parent PAH [8].…”
Section: Microbial Community Characterizationmentioning
confidence: 99%
“…Carmichael and F.K. Pfaender contaminated [27,32,33] and uncontaminated soils/sediments [14]. This is one of the first reports, however, of extensive mineralization of chrysene.…”
Section: Microbial Community Characterizationmentioning
confidence: 99%